Wqˡ-regularity of solutions to systems of partial differential equations - Kopylov, A.P. (Нелинейные граничные задачи, 2004)
We obtain a solution, in a sense final from the standpoint of the theory of Sobolev spaces, to the problem of Wqˡ-regularity of solutions to a system of (generally) nonlinear partial differential equations in the case where the system is locally close to elliptic systems of linear equations with constant coefficients (see Theorem 9). This result gives a number of important consequences for solutions as to nonlinear systems as to linear systems.